Applying Eco Enzyme to Reduce Chemical Oxygen Demand (COD) Content of Artificial River Water - Yonik Meilawati Yustiani; Fadjari Lucia Nugroho; Fauzi Zaki Murtadho; Achmad Teguh Djayadisastra (Journal of Engineering and Technological Sciences, 2023)
Eco enzyme is claimed to improve the quality of polluted water. However, the low pH of eco enzyme solutions can acidify water. The objective of this study was to investigate the effectiveness of eco enzyme in reducing the COD of river water and its effect on the pH of sterilized synthetic river water. The effect of 0.01%, 0.5%, and 1% enzyme concentrations on the COD and pH of synthetic river water with an initial COD of 240 mg/l was investigated. The results showed that eco enzyme itself has high concentration of COD and low pH. The undiluted eco enzyme increased the COD and decreased the pH of both neutralized and non-neutralized synthetic river water. At a 1% eco enzyme concentration and neutral pH, the COD increased in the beginning of experiment and had decreased only by 31.7% after 6-8 days. The COD concentration in this steady state condition had a higher value than that of the initial COD concentration in the river water. This study showed that adding only eco enzyme to synthetic river water is not effective in reducing its COD content.